DEVELOPING MATHEMATICAL COMMUNICATION AND REPRESENTATION OF STUDENTS GRADE VII: A DESIGN RESEARCH - Juandi, Dadang; Jupri, Al (Faculty of Mathematics and Science Education, Universitas Pendidikan Indonesia, 2013)
ABSTRAKPenelitian ini berfokus pada komunikasi matematika dan representasi melalui pembelajaran berbasis masalah yang dikembangkan melalui penelitian desain. Ada dua tujuan dari penelitian ini. Pertama, dalam jangka pendek, penelitian ini dilakukan untuk mengetahui: bagaimana komunikasi matematika dan representasi siswa berkembang, apakah budaya kelas mendukung pencapaian kompetensi dasar-, dan apa hambatan siswa untuk belajar. Kedua, dalam jangka panjang, penelitian ini dilakukan untuk mengembangkan â€œteoriâ€ dalam pendidikan matematika. Kedua tujuan tersebut diharapkan dapat dicapai melalui penelitian pengembangan (dalam hal ini menggunakan desain penelitian). Tujuan pertama dicapai dengan desain penelitian yang meliputi tiga tahap: desain awal, eksperimen, dan analisis retrospektif. Penelitian awal menunjukkan bahwa: (i) komunikasi matematika dan representasi dapat dikembangkan melalui bahan pembelajaran kontekstual, intervensi guru yang tepat itu, berbagai pengaturan belajar-mengajar, situasi didactical dikembangkan oleh guru, dan usaha guru dalam menghubungkan situasi didactical yakni antara bahan dan siswa belajar, dan antara mahasiswa dan guru, (ii) kesulitan siswa meliputi: kesulitan dalam berkomunikasi ide matematika secara lisan, mewakili ide matematika aljabar, menggunakan representasi matematis untuk memecahkan masalah, dan mengusulkan argumentasi, dan (iii) kesulitan guru adalah menganalisis komunikasi matematika dan representasi siswa.ABSTRACTThis research studies mathematical communication and representation through problem based-learning which is developed by design research. There are two objectives of this research. First, in short term, the research is conducted to know: how studentsâ€™ mathematical communication and representation develops, does classroom culture support the achievement of basic-competence, and what are studentsâ€™ learning obstacles. Second, in long term, this research is conducted to develop â€œa theoryâ€ in mathematics education. These two objectives are expected to be achieved through developmental research (in this case using design research). The first objective is achieved by design research which includes three phases: preliminary design, experiment, and retrospective analysis. The preliminary research showed that: (i) mathematical communication and representation could be developed through contextual learning materials, proper teacherâ€™s intervention, various learning-teaching settings, a didactical situation developed by the teacher, and the teacherâ€™s effort in connecting didactical situations i.e., between learning materials and students, and between students and the teacher; (ii) studentsâ€™ difficulties include: a difficulty in communicating mathematical idea verbally, representing mathematical idea algebraically, using mathematical representation to solve problems, and proposing argumentation; and (iii) the teacherâ€™s difficulty is analyzing studentsâ€™ mathematical communication and representations.